S124 Multi-centre reproducibility of 19F-MR ventilation imaging in healthy volunteers. (12th November 2019) - Pippard, B; Neal, M; Maunder, A; Lawson, R; Simpson, AJ; Wild, J; Thelwall, P
Abstract : Introduction: 19 F-MRI of inhaled perfluoropropane (PFP) is a relatively new approach to ventilation imaging, enabling assessment of regional gas distribution without the requirement for hyperpolarization. 1 While quantitative measures of pulmonary ventilation (e.g. the percent ventilated lung volume, %VV) are well established for hyperpolarized-gas MRI, 2 their utility in 19 F-MR ventilation imaging is less clear. Determining the reproducibility of such measures is paramount in developing future clinical application of this technique. Aim: We assessed the reproducibility of%VV measurements in healthy volunteers using 19 F-MRI of inhaled PFP across two UK study sites. Methods: 38 healthy volunteers (20M, 18F; aged 23–67) provided written informed consent and were screened for eligibility at one of two UK study sites. Participants underwent a single MRI scan session on a 3T scanner, involving periodic inhalation of a 79% PFP/21% oxygen gas mixture. Each gas inhalation lasted <1 min, comprising three deep breaths of gas followed by a breath-hold (∼13.5s), during which 19 F-MR images were acquired. Participants underwent four 19 F-MRI acquisitions in total, each separated by a 5 min interval.%VV values were determined by registering ventilation images to anatomical 1 H images (acquired separately for each participant) and semi-automated image segmentation performed by two independent raters. Intra-volunteer%VV reproducibility was assessed using a two-way random measures Intraclass Correlation Coefficient, ICC(2, 1). Inter-rater reliability was evaluated using the Dice Similarity Coefficient (DSC). Results: MRI scans were well tolerated throughout with no adverse events. Assessment of intra-volunteer%VV reproducibility revealed an ICCrater1 =0.682 (95% CI=0.529–0.785) and ICCrater2 =0.614 (0.443–0.736). Assessment of inter-rater reliability of%VV measurements showed a high mean DSC(±SD) of 0.97±0.2, with only minor discrepancies between the two raters (figure 1). Conclusions: We have demonstrated good reproducibility of%VV measurements in healthy volunteers using 19 F-MRI of inhaled PFP. Importantly, our methods have been successfully implemented across two UK study sites, confirming suitability for multi-centre use and the development of larger clinical trials. Current studies will apply these techniques to quantify ventilation impairment in patients with asthma and COPD, including assessing response to bronchodilator therapy. References: Gutberlet M, et al . Radiology 2018;286:1040–1051 Kirby M, et al . Radiology 2012;265:600–610